Insights Into the Binding Mechanism of GC7 to Deoxyhypusine Synthase in Sulfolobus solfataricus: A Thermophilic Model for the Design of New Hypusination Inhibitors - D'Agostino, Mattia; Motta, Stefano; Romagnoli, Alice; Orlando, Patrick; Tiano, Luca; La Teana, Anna; Di Marino, Daniele (Frontiers in Chemistry, 2020)
Translation factor 5A (eIF5A) is one of the most conserved proteins involved in protein synthesis. It plays a key role during the elongation of polypeptide chains and its activity is critically dependent on hypusination, a post-translational modification of a specific lysine residue through two consecutive enzymatic steps carried out by deoxyhypusine synthase (DHS), with spermidine as substrate, and deoxyhypusine hydroxylase (DOHH). It is well established that eIF5A is overexpressed in several cancer types and it is involved in various diseases such as HIV-1 infection, malaria and diabetes therefore the development of inhibitors targeting both steps of the hypusination process is considered as a promising and challenging therapeutic strategy. One of the most efficient inhibitors of the hypusination process is the spermidine analogue N1-guanyl-1,7-diaminoheptane (GC7). GC7 interacts in a specific binding pocket of the DHS completely blocking its activity however its therapeutic use is limited by poor selectivity and restricted bioavability. Here we have performed a comparative study between human DHS (hDHS) and archaeal DHS from crenarchaeon Sulfolobus solfataricus (aDHS) to understand the structural and dynamical features of the GC7 inhibition. The advanced Metadynamics (MetaD) classical molecular dynamics simulations show that the GC7 interaction is less stable in the thermophilic enzyme compared to hDHS that could underlie a lower inhibitory capacity of the hypusination process in Sulfolobus solfataricus. To confirm this hypothesis, we have tested GC7 activity on S. solfataricus by measuring cellular growth and results have shown lack of inhibition of aIF5A hypusination in contrast to the established effect on eukaryotic cellular growth. These results provide for the first time detailed molecular insights into the binding mechanism of GC7 to aDHS generating the basis for the design of new and more specific DHS inhibitors.